2016
DOI: 10.1002/1873-3468.12442
|View full text |Cite
|
Sign up to set email alerts
|

miR‐296 inhibits proliferation and induces apoptosis by targeting FGFR1 in human hepatocellular carcinoma

Abstract: MiR-296 was previously reported to be underexpressed in hepatocellular carcinoma (HCC). However, the clinical value of miR-296 and its function in HCC remain poorly understood. In this study, we found that miR-296 levels are decreased in HCC specimens and cells, and that the underexpression of miR-296 is associated with adverse clinical parameters and poor overall survival rate. In vitro experiments indicate that miR-296 inhibits proliferation, colony formation, and cell cycle progression, and enhances apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…The function of FGFR1 in HCC was substantially uncovered in previous studies. For example, FGFR1 restoration promoted HCC cell proliferation and cell cycle progression but limited apoptosis [30]. Keratin 19 silence could weaken the expression of FGFR1, leading to the inhibition of HCC cell growth and the promotion of cell apoptosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…The function of FGFR1 in HCC was substantially uncovered in previous studies. For example, FGFR1 restoration promoted HCC cell proliferation and cell cycle progression but limited apoptosis [30]. Keratin 19 silence could weaken the expression of FGFR1, leading to the inhibition of HCC cell growth and the promotion of cell apoptosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…As an important subgroup of short noncoding RNAs, micro-RNAs (miRs) play essential roles in a large array of physiologic and pathologic conditions in which their aberrant expression has been correlated with disease pathogenesis and progression, including fibrogenesis (14,15). As previously reported by Wang et al (16), the low expression of miR-296 has been earmarked as a responsible element associated with unfavorable survival rates and poor prognoses among patients with hepatocellular carcinoma, whereas up-regulated expression levels of miR-296 exhibit tumor suppressor capabilities. Additionally, evidence has been presented indicating that DOK1 and DOK2 contribute to progressive fibrosis (17).…”
mentioning
confidence: 93%
“…As previously reported by Wang et al . (16), the low expression of miR‐296 has been earmarked as a responsible element associated with unfavorable survival rates and poor prognoses among patients with hepatocellular carcinoma, whereas up‐regulated expression levels of miR‐296 exhibit tumor suppressor capabilities. Additionally, evidence has been presented indicating that DOK1 and DOK2 contribute to progressive fibrosis (17).…”
mentioning
confidence: 99%
“…Recent studies have reported that miR‐296‐5p could participate in the initiation and progression of several types of human diseases, particularly cancers. For instance miR‐296 exerted a tumour suppressive role in hepatocellular carcinoma (HCC) by targeting fibroblast growth factor receptor 1 and suppressing the proliferation of HCC cells . In addition, the expression of miR‐296‐5p in liver samples of patients with nonalcoholic steatohepatitis was lower than that in patients with simple steatosis or the control group.…”
Section: Discussionmentioning
confidence: 99%